PROBLEMA ANTREPRENORIATULUI DIN PERSPECTIVA EXPERIENŢELOR EDUCAŢIONALE - USM ADMIN (Moldova State University, 2010)
The entrepreneurial education is a new orientation in the field of education, actively promoted by the European Commission, sustaining the creation of multiple ideas and didactic materials for the consolidation of business mentality through education. In the main educational purposes there will be included those which focus the forming of the entrep- reneurial competences, those which refer to the initiation in the business world. The entrepreneurial education can be an aspect of education as a school subject and can also be a subject which can offer the students the chance of success in life. If we take into consideration the aspect of the National Curriculum, the entrepreneurial education involves the assimi- lation of knowledge about the specific of a successful business, the development of certain capacities, concerning the ini- tiation and implementation of a business. The economic training, through the entering of the economic factor in educa- tion, directs the students' training on the dimension of culture and entrepreneurial spirit. The basic ideas on which there can be built the curricular aims about forming the entrepreneurial competences focus: the facility of developing the inno- vative practices in the field of professional training, the forming of culture and of entrepreneurial spirit.